Strengthening Organizational Capacity and Empowering Coastal Communities in Sentang Village, Teluk Mengkudu District, Serdang Bedagai Regency - Rosmery; Zulkifli; Purba, Hasim; Ekayanta, Fredick Broven (Talenta Publisher, 2022)
The societies in Sentang Village are an example of coastal community who have been left behind. The majority of people work as fishermen which have experienced a decline in income from fish catches since pandemic Covid-19. To overcome these conditions, this community service strengthens organizational capacity and empowers the community. Through these activities, it is hoped that the community will have an understanding of the importance of organizations to improve their welfare. A strong community organization will be the capital for the community to fight for their interests. Furtermore, this service will provide regular assistance to see the implementation of organizational capacity building and community empowerement.